Antifriction lubricating composite surface based on friction heat driving material phase change and preparation method of antifriction lubricating composite surface
By embedding phase change materials on the friction surface and using friction heat to drive their melting, combined with the dynamic pressure lubrication effect of the surface texture layer, the problem of difficult to effectively reduce friction heat and large wear of solid lubricating materials in the prior art is solved, and efficient friction reduction lubrication effect and environmental protection are achieved.
Patent Information
- Application Number
- CN202510042364.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
While reducing friction heat, the prior art is difficult to effectively reduce the surface temperature of the friction pair, resulting in increased wear of the substrate, and solid lubricating materials such as MoS2 are worn more frequently in actual use and limited service life.
The friction reduction lubrication composite surface based on friction heat-driven phase change is adopted. By setting up a surface texture layer of microstructure on the surface of the substrate, and embedded in the phase change material such as paraffin, crystalline hydrated salt or inorganic salt, the friction heat is used to melt the phase change material to form a liquid lubrication, and a dynamic pressure lubrication effect is generated through the wedge-shaped space formed by non-iso-deep surface texture.
Effectively reduce the surface temperature of the friction pair, reduce friction, improve the wear resistance of the substrate, reduce the use of lubricating oil, and achieve energy saving, emission reduction and consumption reduction. At the same time, the low toxicity and environmental protection of phase change materials further reduce environmental impact.
Smart Images

Figure CN119826078A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a friction-reducing lubricating surface and a preparation method thereof, and in particular to a friction-reducing lubricating composite surface based on friction heat driven material phase change and a preparation method thereof. Background Art
[0002] Dry friction can reduce the use of lubricating oil and may cause up to 95% of mechanical energy to be converted into heat energy, including sliding heat dissipation of friction surface extrusion deformation, chemical heat generation of material interaction, and consumption heat dissipation of phonon-electron coupling, etc. Such friction heat will rapidly increase the temperature of the contact surface, forming a significant temperature gradient, causing problems such as thermoelastic deformation, contact damage, and local melting, thereby aggravating the wear of the substrate and eventually leading to structural failure.
[0003] Generally, the friction heat output can be reduced by reducing the friction coefficient of the friction surface. Studies have shown that MoS2 solid lubricant coatings can effectively reduce friction and friction heat due to their low friction coefficient and easy formation of lubricating films. For example, MoS2 coatings reduce the temperature of cubic boron nitride grinding wheels by 64°C and improve the surface quality of titanium alloy workpieces. At the same time, MoS2 composite coatings and other fiber liners also significantly reduce the friction coefficient and temperature. However, these layered solid lubricants such as MoS2 may cause greater wear in actual use due to their low hardness.
[0004] From another perspective, if the friction heat can be dissipated through rapid conduction, the friction interface can also be kept at a lower temperature. For example, the improvement of MoS2 / Al2O3 / C composite coating and C / MoS2 composite coating has increased thermal conductivity and significantly reduced wear rate. However, solid lubricating materials with layered structures such as MoS2 have low hardness, and in actual use, they wear more and have limited service life.
[0005] It is worth noting that both heat conduction and heat dissipation are passive consumption of friction heat, while actively absorbing and utilizing friction heat is a more sensible choice. Therefore, researchers absorb and utilize friction heat to transform its adverse effects into driving conditions that are favorable for lubrication. For example, by embedding solid lubricants in the micropores of metal ceramics, these lubricants absorb heat and soften during friction to form a lubricating film. However, the amount of friction heat absorbed by solid lubricants without phase change is very limited, and the lubrication effect is not as good as liquid lubrication.
[0006] Phase change materials can change from solid to liquid, and their phase change process absorbs a lot of heat. They have been widely studied in the field of battery thermal management, but there are few reports on related research in the field of friction. At present, only paraffin microcapsules are added to aromatic thermosetting copolyesters, but the microcapsules do not break and cannot release paraffin. Summary of the invention
[0007] Purpose of the invention: The purpose of the present invention is to provide a friction-reducing and lubricating composite surface based on friction heat driven material phase change that can achieve temperature reduction and wear reduction;
[0008] The second object of the present invention is to provide a method for preparing the above-mentioned friction-reducing and lubricating composite surface based on friction-heat-driven material phase change.
[0009] Technical solution: The friction-reducing and lubricating composite surface based on friction heat driven material phase change described in the present invention includes a substrate, a surface texture layer with a microstructure arranged on the surface of the substrate, and the surface texture layer has a space formed by an equal depth structure or a non-equal depth structure; the surface texture layer is embedded with a phase change material.
[0010] The isobath structure refers to a structure whose bottom surface is a plane, and the non-isodepth structure refers to a structure whose bottom surface is an inclined surface. When the bottom surface is an inclined surface, the space formed is a wedge-shaped space.
[0011] Wherein, a hard film layer is provided on the surface texture layer.
[0012] Wherein, the phase change material is at least one of paraffin with a phase change temperature range of 15 to 100°C, a crystalline hydrated salt with a phase change temperature range of 0 to 100°C, or an inorganic salt with a phase change temperature range of 100 to 700°C; the crystalline hydrated salt is LiClO3·3H2O and / or ZnCl2·3H2O; the inorganic salt is LiNO3-KNO3 and / or NaNO3-KNO3.
[0013] The phase change material is a mixed phase change material mixed with thermal conductive particles; the thermal conductive particles are at least one of Al2O3, SiC or graphene. The types of phase change material and thermal conductive particles should be determined according to the working temperature of the friction pair surface and the duration of the startup phase; the phase change temperature of the phase change material should be lower than the working temperature of the friction pair surface, and the shorter the startup phase, the higher the thermal conductivity of the thermal conductive particles should be.
[0014] Wherein, the width of the texture is 200 μm to 1000 μm; the surface density of the texture is 10% to 40%; and the depth of the texture is 150 μm to 1000 μm.
[0015] The shape of the surface texture is one of a circle, a triangle, a square or a rhombus; the depth, surface density, width and diameter of the surface texture can be changed and set according to needs.
[0016] Wherein, the hard film is a metal or non-metal single substance or compound coating.
[0017] Wherein, the substrate is a composite material of at least two of one or more of metal materials, inorganic non-metal materials or organic polymer materials.
[0018] The method for preparing the friction-reducing and lubricating composite surface based on friction heat driven material phase change comprises the following steps:
[0019] (1) Processing a surface texture with a microstructure on the substrate surface;
[0020] (2) Embedding molten phase change material into surface texture by ultrasonic degassing;
[0021] (3) Cooling and solidifying the surface film texture sample with embedded phase change material and polishing it to remove excess phase change material on the surface, thereby obtaining the friction-reducing and lubricating composite surface based on friction heat driven material phase change.
[0022] Wherein, in step (1), the surface texture is obtained by any one of micro-cutting, micro-grinding, micro-abrasive jet machining, laser machining, electrospark machining, LIGA, UV lithography, reactive ion etching, ultrasonic machining, surface shot peening or surface embossing.
[0023] As a preferred embodiment, when a hard film layer is provided on the surface texture layer, the method for preparing the friction-reducing and lubricating composite surface based on friction heat driven material phase change comprises the following steps:
[0024] (1) Processing a surface texture with a microstructure on the substrate surface;
[0025] (2) preparing a hard film layer on a surface textured substrate;
[0026] (3) Embedding molten phase change material into surface texture by ultrasonic degassing;
[0027] (4) Cooling and solidifying the surface film texture sample with embedded phase change material and polishing it to remove excess phase change material on the surface, thereby obtaining the friction-reducing and lubricating composite surface based on friction heat driven material phase change.
[0028] Wherein, in step (2), the hard film is prepared by any one of physical vapor deposition, chemical vapor deposition, thermal spraying, electroplating, chemical plating or laser cladding methods.
[0029] Principle of the invention: The present invention introduces phase change material into the friction surface to absorb friction heat, reduce the surface temperature of the friction pair, and use the friction heat to melt the phase change material. At the same time, the convenient storage of the coupled surface texture and the dynamic pressure lubrication effect generated by the wedge-shaped space formed by the non-uniform depth surface texture are used to lubricate the friction surface.
[0030] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:
[0031] (1) The present invention combines a surface texture with a spatial storage function to construct a composite surface of a texture / phase change material, which can not only store the phase change material and control its release rate during the friction process, but also utilize the friction heat generated on the friction pair surface to melt the phase change material into a liquid to form liquid lubrication during the friction process, and then couple the wedge-shaped space formed by the non-uniform depth surface texture to generate a dynamic pressure lubrication film to reduce friction and lubricate the friction pair surface, thereby reducing the use of lubricating oil on the friction pair surface and reducing the temperature of the friction pair interface by absorbing heat from the phase change material, thereby achieving energy saving, emission reduction, and consumption reduction; (2) In order to further improve the wear resistance of the textured surface, a hard film with excellent wear resistance is provided on the textured surface, and a film texture surface with a phase change material embedded therein is proposed; (3) The melting point of the phase change material can be selected as a single type according to the actual operating temperature of the friction pair interface, or a mixture of multiple phase change materials can be used. (4) The thermal conductivity of phase change materials is low. In order to accelerate the phase change process, the thermal conductive particles in the composite phase change material can be selected according to the start-up time of the friction pair interface, such as Al2O3 (30W / m·K), SiC (490W / m·K), and graphene (5000W / m·K); (5) Phase change materials are mostly relatively environmentally friendly lubricants with low toxicity and environmental impact. Compared with some synthetic lubricants, they have less burden on the environment and can be recycled and reused after use, further reducing environmental impact. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the process of the present invention;
[0033] Figure 2 is the friction coefficient of the surface texture with or without paraffin in Example 1 of the present invention;
[0034] Figure 3 is the wear amount of the surface texture with or without paraffin in Example 1 of the present invention;
[0035] Figure 4 is the temperature of the surface texture with or without paraffin in Example 1 of the present invention;
[0036] Figure 5 is the wear amount of paraffin wax on the surface textures of different sizes in Example 2 of the present invention;
[0037] Figure 6 is the wear amount of the surface textured with paraffin wax of different shapes in Example 3 of the present invention;
[0038] Figure 7 is the friction coefficient of the surface texture with or without paraffin in Example 4 of the present invention;
[0039] Figure 8is the wear amount of the surface texture with or without paraffin in Example 4 of the present invention;
[0040] Fig. 9 is the temperature of the surface texture with or without paraffin in Example 4 of the present invention;
[0041] Fig.10 is the friction coefficient of the surface film texture with or without paraffin in Example 5 of the present invention;
[0042] Fig.11 is the wear amount of the surface film texture with or without paraffin in Example 5 of the present invention;
[0043] Fig.12 is the temperature of the surface film texture with or without paraffin in Example 5 of the present invention;
[0044] Fig.13 Schematic diagram of surface texture filling with paraffin in Example 6 of the present invention. DETAILED DESCRIPTION
[0045] The present invention is described in further detail below.
[0046] Example 1
[0047] like Figure 1 As shown, the present invention provides a method for preparing a friction-reducing and lubricating composite surface based on friction heat driven material phase change, comprising the following steps:
[0048] (1) Texture processing: The diamond texture with a side length of 0.2 mm, a surface density of 10%, and a depth of 0.15 mm was processed on the surface of TC4 titanium alloy with a diameter of 30 mm and a height of 6 mm using micro-EDM technology;
[0049] (2) Embedded paraffin: The prepared texture sample is placed in a molten paraffin solution and degassed using an ultrasonic degasser for 20 min to allow the molten paraffin to be completely embedded in the texture;
[0050] (3) Take out the sample, cool it, and polish it to remove excess paraffin on the surface to obtain a texture sample with paraffin embedded in it.
[0051] The friction test was carried out on the surface with or without paraffin wax texture prepared in the above steps under the conditions of load of 12N, grinding speed of 0.2m / s and sliding distance of 1000m, and the friction coefficient, wear amount and temperature were compared:
[0052] ① Friction coefficient: During the friction test, the friction coefficient of the surface texture with or without paraffin is Figure 2 The average friction coefficient of the texture without paraffin is 0.42, and the average friction coefficient of the texture with paraffin is 0.28, which is 33.3% lower than that of the texture without paraffin, indicating that the phase change material paraffin can effectively reduce the friction coefficient of the alloy substrate surface.
[0053] ② Wear amount: Use AL104-IC electronic balance to test the wear amount of wax texture after friction test. Figure 3 The wear loss of the texture without wax is 13.6 mg, and the wear loss of the texture with wax is 8.6 mg, which is 36.8% lower than that of the texture without wax, indicating that the phase change material wax improves the wear resistance of the alloy substrate.
[0054] ③ Temperature: The actual friction interface temperature of the friction test with or without wax texture was measured using an infrared spectrometer. Figure 4 The temperature of the structure without wax texture gradually rises and then stabilizes at about 42°C, while the temperature of the structure with wax texture gradually rises and then stabilizes at about 41°C, indicating that the phase change material wax can improve the heat conduction of the friction pair and reduce the friction interface temperature.
[0055] Example 2
[0056] A method for preparing a friction-reducing and lubricating composite surface based on friction heat driven material phase change comprises the following steps:
[0057] (1) Texture processing: The diamond texture with different size parameters was processed on the surface of TC4 titanium alloy with a diameter of 30 mm and a height of 6 mm by micro-EDM technology. The specific size parameters are shown in Table 1.
[0058] Table 1
[0059] Code Texture width / μm Texture depth / μm Texture density / % R1 250 150 10 R2 200 150 10 R3 200 250 10 R4 250 250 25
[0060] (2) Embedded paraffin: The prepared different texture samples were placed in the molten paraffin solution respectively, and degassed by ultrasonic degasser for 20 min to make the molten paraffin completely embedded in the texture;
[0061] (3) Take out the sample, cool it, and polish it to remove excess paraffin on the surface to obtain different paraffin-embedded texture samples.
[0062] The paraffin wax texture surfaces of different sizes prepared in the above steps were subjected to friction tests at a load of 12N, a grinding speed of 0.2m / s, and a sliding distance of 1000m, and the wear amounts were compared: the wear amounts of paraffin wax texture surfaces of different sizes after the friction tests were tested using an AL104-IC electronic balance. Figure 5 The wear loss of R1, R2, R3, and R4 with wax texture are 12.5 mg, 8.6 mg, 7.3 mg, and 10.6 mg, respectively. By comparing the changes in texture width, depth, surface density, and wear loss, it can be seen that the decrease in texture width and texture surface density and the increase in texture depth will lead to a decrease in the wear loss of the wax-textured specimens.
[0063] Example 3
[0064] A method for preparing a friction-reducing and lubricating composite surface based on friction heat driven material phase change comprises the following steps:
[0065] (1) Texture processing: Laser processing technology is used to process circular, diamond, square, triangle, and elliptical textures with a surface density of 30.7% and a depth of 0.5 mm on the surface of 7075 aluminum alloy with a diameter of 30 mm and a height of 4 mm;
[0066] (2) Embedded paraffin: The prepared texture sample is placed in a molten paraffin solution and degassed using an ultrasonic degasser for 20 min to allow the molten paraffin to be completely embedded in the texture;
[0067] (3) Take out the sample, cool it, and polish it to remove excess paraffin on the surface to obtain a texture sample with paraffin embedded in it.
[0068] The paraffin wax texture surface prepared in the above steps was subjected to friction test under the conditions of 9N load, 0.4m / s grinding speed and 1000m sliding distance, and the wear amount was compared: the wear amount of paraffin wax textures of different shapes after the friction test was tested by AL104-IC electronic balance. Figure 6 The wear amounts of the circular, diamond, square, triangle, and elliptical wax textures are 1.7 mg, 2.0 mg, 1.4 mg, 1.5 mg, and 4.4 mg, respectively. It is found that the wear amounts of the square and triangle textures are smaller, and the wear amount of the square texture is the smallest.
[0069] Example 4
[0070] A method for preparing a friction-reducing and lubricating composite surface based on friction heat driven material phase change comprises the following steps:
[0071] (1) Texture processing: Laser processing technology is used to process a circular texture with a diameter of 0.5 mm, a surface density of 30.7%, and a depth of 0.5 mm on the surface of 7075 aluminum alloy with a diameter of 30 mm and a height of 4 mm;
[0072] (2) Embedded paraffin: The prepared texture sample is placed in a molten paraffin solution and degassed using an ultrasonic degasser for 20 min to allow the molten paraffin to be completely embedded in the texture;
[0073] (3) Take out the sample, cool it, and polish it to remove excess paraffin on the surface to obtain a texture sample with paraffin embedded in it.
[0074] The friction test was carried out on the surface with or without wax texture prepared in the above steps under the conditions of load of 9N, grinding speed of 0.4m / s and sliding distance of 1000m, and the friction coefficient and wear amount were compared:
[0075] ① Friction coefficient: During the friction test, the friction coefficient of the surface texture with or without paraffin is Figure 7 The average friction coefficient of the texture without paraffin is 0.23, and the average friction coefficient of the texture with paraffin is 0.07, which is 69.6% lower than that of the texture without paraffin, indicating that the phase change material paraffin can effectively reduce the friction coefficient of the alloy substrate surface.
[0076] ② Wear amount: Use AL104-IC electronic balance to test the wear amount of wax texture after friction test. Figure 8 The wear loss of the texture without wax is 11.2 mg, and the wear loss of the texture with wax is 3.4 mg, which is 69.6% lower than that of the texture without wax, indicating that the phase change material wax improves the wear resistance of the alloy substrate.
[0077] ③ Temperature: The actual friction interface temperature of the friction test with or without wax texture was measured using an infrared spectrometer. Fig. 9 The temperature of the structure without wax texture gradually rises and then stabilizes at about 41°C, while the temperature of the structure with wax texture gradually rises and then stabilizes at about 40°C, indicating that the phase change material wax can improve the heat conduction of the friction pair and reduce the friction interface temperature.
[0078] Example 5
[0079] A method for preparing a friction-reducing and lubricating composite surface based on friction heat driven material phase change comprises the following steps:
[0080] (1) Texture processing: Micro-EDM processing technology is used to process a groove texture with a width of 0.3 mm, a surface density of 10%, and a depth of 0.2 mm on the surface of TC4 titanium alloy with a diameter of 30 mm and a height of 6 mm;
[0081] (2) Film preparation: A 3 μm thick diamond-like carbon (DLC) film was deposited on the textured surface using enhanced magnetron cathode arc coating technology;
[0082] (3) Embedded paraffin: Place the prepared surface film texture sample into a molten paraffin solution and use an ultrasonic degasser to degas for 20 min to allow the molten paraffin to be completely embedded in the surface film texture;
[0083] (4) Take out the sample, cool it, and polish it to remove excess paraffin on the surface to obtain a surface film texture sample with paraffin embedded in it.
[0084] The friction test was carried out on the surface with or without paraffin film texture prepared in the above steps under the conditions of load of 9N, grinding speed of 0.4m / s and sliding distance of 1000m, and the friction coefficient and wear amount were compared:
[0085] ① Friction coefficient: During the friction test, the friction coefficient of the surface film texture with or without paraffin is Fig.10 The average friction coefficient of the film texture without paraffin is 0.08, and the average friction coefficient of the film texture with paraffin is 0.05, which is 37.5% lower than that of the film texture without paraffin, indicating that the phase change material paraffin can effectively reduce the friction coefficient of the alloy substrate surface.
[0086] ② Wear amount: Use AL104-IC electronic balance to test the wear amount of the paraffin film texture after the friction test. Fig.11 The wear loss of the film texture without paraffin is 2.5 mg, and the wear loss of the film texture with paraffin is 1.76 mg, which is 29.6% lower than that of the film texture without paraffin, indicating that the phase change material paraffin improves the wear resistance of the alloy substrate.
[0087] ③ Temperature: The actual friction interface temperature of the friction test with or without paraffin film texture was measured using an infrared spectrometer. Fig.12 The temperature of the texture without paraffin film gradually rises and then stabilizes at about 42°C, while the temperature of the texture with paraffin film gradually rises and then stabilizes at about 41°C, indicating that the phase change material paraffin can improve the heat conduction of the friction pair and reduce the friction interface temperature.
[0088] Example 6
[0089] A method for preparing a friction-reducing and lubricating composite surface based on friction heat driven material phase change comprises the following steps:
[0090] (1) Texture processing: The diamond texture with a side length of 0.25 mm, a surface density of 20%, and a depth of 0.25 mm was processed on the surface of TC4 titanium alloy with a diameter of 30 mm and a height of 6 mm by using micro-electrodischarge forming technology;
[0091] (2) Embedded paraffin: Place the prepared texture sample into the molten paraffin solution and degas it using an ultrasonic degasser for 20 min;
[0092] (3) Take out the two samples, cool them, and polish them to remove excess paraffin on the surface to obtain texture samples with paraffin embedded in them.
[0093] Comparative Example 1
[0094] On the basis of Example 6, the difference from Example 6 is that in step (2), paraffin is embedded using a common filling method, that is, the prepared texture sample is placed in a stationary molten paraffin solution for natural embedding.
[0095] like Fig.13As shown, by comparing the SEM photos of the two embedding methods of Example 6 and Comparative Example 1, it can be found that the ultrasonic degasser effectively removes the bubbles in the paraffin through the high-frequency vibration of ultrasound, and can effectively and evenly fill the white paraffin into the formed microstructure; while in the conventional method, the bubbles will remain in the surface texture and the paraffin cannot enter the surface texture.
Claims
1. A friction-reducing and lubricating composite surface based on friction heat driven material phase change, characterized in that: The invention comprises a substrate, a surface texture layer with a microstructure arranged on the surface of the substrate, the surface texture layer having a space formed by an iso-depth structure or a non-iso-depth structure; and the surface texture layer is embedded with a phase change material.
2. The friction-reducing and lubricating composite surface based on friction heat driven material phase change according to claim 1, characterized in that: A hard film layer is arranged on the surface texture layer.
3. The friction-reducing and lubricating composite surface based on friction heat driven material phase change according to claim 1, characterized in that: The phase change material is at least one of paraffin with a phase change temperature range of 15-100°C, crystalline hydrated salt with a phase change temperature range of 0-100°C, and inorganic salt with a phase change temperature range of 100-700°C.
4. The friction-reducing and lubricating composite surface based on friction heat driven material phase change according to claim 1, characterized in that: The width of the texture is 200 μm to 1000 μm; the surface density of the texture is 10% to 40%; and the depth of the texture is 150 μm to 1000 μm.
5. The friction-reducing and lubricating composite surface based on friction heat driven material phase change according to claim 1, characterized in that: The phase change material is a mixed phase change material mixed with thermal conductive particles; the thermal conductive particles are at least one of Al2O3, SiC or graphene.
6. The friction-reducing and lubricating composite surface based on friction heat driven material phase change according to claim 1, characterized in that: The surface texture has a shape of at least one of a circle, a triangle, a square or a rhombus.
7. The friction-reducing and lubricating composite surface based on friction heat driven material phase change according to claim 2, characterized in that: The hard film is a metal or non-metal simple substance or compound coating; the substrate is at least one of a metal material, an inorganic non-metal material or an organic polymer material.
8. A method for preparing a friction-reducing and lubricating composite surface based on phase change of friction-heat-driven materials as claimed in claim 1, characterized in that: The following steps are involved: (1) Processing a surface texture with a microstructure on the substrate surface; (2) Embedding molten phase change material into surface texture by ultrasonic degassing; (3) Cooling and solidifying the surface film texture sample with embedded phase change material and polishing it to remove excess phase change material on the surface, thereby obtaining the friction-reducing and lubricating composite surface based on friction heat driven material phase change.
9. A method for preparing a friction-reducing and lubricating composite surface based on phase change of friction-heat-driven materials as claimed in claim 2, characterized in that: The following steps are involved: (1) Processing a surface texture with a microstructure on the substrate surface; (2) preparing a hard film layer on a surface textured substrate; (3) Embedding molten phase change material into surface texture by ultrasonic degassing; (4) Cooling and solidifying the surface film texture sample with embedded phase change material and polishing it to remove excess phase change material on the surface, thereby obtaining the friction-reducing and lubricating composite surface based on friction heat driven material phase change.
10. The method for preparing a friction-reducing and lubricating composite surface based on friction heat driven material phase change according to any one of claims 8 or 9, characterized in that: In step (1), the surface texture is obtained by any one of micro-machining, micro-grinding, micro-abrasive jet machining, laser machining, electrospark machining, LIGA, UV lithography, reactive ion etching, ultrasonic machining, surface shot peening or surface embossing.